Surveillance of Suicidal and Nonsuicidal Self-Injury in the New York City Jail System. (April 2014) - Selling, Daniel; Solimo, Angela; Lee, David; Horne, Kerry; Panove, Elena; Venters, Homer
Suicide and nonsuicidal self-injury represent significant causes of morbidity and mortality in jail settings. The New York City Department of Health and Mental Hygiene instituted a database of suicidal and nonsuicidal self-injuries in 2007. Between 2007 and 2011, there were eight deaths by suicide and 2, 514 acts of self-injury, with the annual rate of self-injury increasing significantly throughout this time period. The most frequent methods of self-injury were lacerations (816), ligature tied around the neck (569), attempted overdose (501), and swallowed foreign objects (372). This review led to improvements in surveillance as well as improvement of the newly implemented electronic health record.